Competition, market power and third-party tracking - Ezrachi, A; Robertson, V (Kluwer Law International, 2019)
The prevalence of third-party tracking in our modern ecosystem cannot be ignored. Trackers, on our websites and apps, enable multi-sourced data gathering, at distinct volume, variety, velocity and veracity. While numerous operators engage in tracking, the majority of these trackers are controlled by a small number of data giants. In this article we consider the rise and growth of this industry, the power it has bestowed on a handful of platforms, and the possible implications for consumer welfare and competition.